Intimacy, isolation and attitudes towards aging among homosexuals. - Lebrilla, Tazjana D.
This study presented in-depth accounts of the experiences of homosexual adults regarding their intimate intimate relationships, their of isolation and their attitudes toward aging. It also included the lifestyle of homosexuals and the changes that are perceived to happen. The study conducted is fully a case study research design. The study of six (6) homosexuals and the respondents were chosen within the Province of Iloilo, Panay. Thorough interviews were conducted to each individual and the data gathered was analyzed., The results of the phenomenological study acquired supported the theories used in the study and it produced significant and novel results regarding the lives of homosexuals. The results showed that homosexuals often lead lives marked by secrecy. The ideas they have acquired on intimacy and isolation laid ground for their expectations, goals and attitudes. They have positive attitudes towards aging and they see no great difference in the manner by which heterosexuals and homosexuals age.